Online Resources: Digital Materials: China and Japan. (Religious Studies Review (John Wiley & Sons, Inc.), 2021)
The article reviews several web sites including "Religion and Politics", "Sociology of Religion Resources", and "AnthroSource" located at www.religionandpolitics.org, https://www.sociologyofreligion.net, and https://anthrosource.onlinelibrary.wiley.com/hub/.